The reliability of a linear position transducer for measuring countermovement jump performance in national-level road cyclists - Turner, A.; McKean, M.; Doyle, D.; Burkett, B. (PLOS ONE, 2024)
Background Jump tests have applications in fatigue monitoring, training intervention evaluations, and talent identification in cycling populations. Due to competitive cycling`s inherent travel demands, linear position transducers (LPTs) are suitable for assessing jump performance in this population as they are a mobile and validated technology. Understanding the reliability and sensitivity of LPTs in assessing jump performance in cycling populations is required to support the development of sports science protocols. Using an LPT, this study aimed to determine the reliability and sensitivity of countermovement jump (CMJ) variables in road cyclists.